Potential spreading risks and disinfection challenges of medical wastewater by the presence of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) viral RNA in septic tanks of Fangcang Hospital - Zhang, Dayi; Ling, Haibo; Huang, Xia; Li, Jing; Li, Weiwei; Yi, Chuan; Zhang, Ting; Jiang, Yongzhong; He, Yuning; Deng, Songqiang; Zhang, Xian; Wang, Xinzi; et al. (The Science of the total environment, 2020)
The outbreak of coronavirus infectious disease-2019 (COVID-19) pneumonia raises the concerns of effective deactivation of the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) in medical wastewater by disinfectants. In this study, we evaluated the presence of SARS-CoV-2 viral RNA in septic tanks of Wuchang Cabin Hospital and found a striking high level of (0.5–18.7) × 103 copies/L after disinfection with sodium hypochlorite. Embedded viruses in stool particles might be released in septic tanks, behaving as a secondary source of SARS-CoV-2 and potentially contributing to its spread through drainage pipelines. Current recommended disinfection strategy (free chlorine ≥0.5 mg/L after at least 30 min suggested by World Health Organization; free chlorine above 6.5 mg/L after 1.5-h contact by China Centers for Disease Control and Prevention) needs to be reevaluated to completely remove SARS-CoV-2 viral RNA in non-centralized disinfection system and effectively deactivate SARS-CoV-2. The effluents showed negative results for SARS-CoV-2 viral RNA when overdosed with sodium hypochlorite but had high a level of disinfection by-product residuals, possessing significant ecological risks. [Display omitted] •First report on disinfection performance for SARS-CoV-2 in medical wastewater•Incomplete removal of SARS-CoV-2 RNA under WHO guideline•High level of DBPs when SARS-CoV-2 is completed removed.